Recurrent isolated tuberculous inguinal lymphadenopathy : A case report and review of literature - Asuquo, Maurice; Ugbem, Theophilus; Marwa, Adams (International Journal of Medicine, 2017)
Chronic peripheral lymphadenopathy is indicative of pathology of which tuberculosis is the commonest. Isolated inguinal tuberculous lymphadenitis is a rare finding. Presented is a healthy looking 16 year old human immunodeficiency virus seronegative male with recurrent isolated tuberculous left inguinal lymphadenopathy. Physicians are requested to consider tuberculosis as differential diagnosis of inguinal lymphadenopathy and to subject same to histological evaluation for proper diagnosis and treatment.